A Common Clinical Dilemma: Management of Abnormal Vaginal Cytology and Human Papillomavirus Test Results. Issue 2 (April 2016) - Khan, Michelle J.; Massad, L. Stewart; Kinney, Walter; Gold, Michael A.; Mayeaux, EJ; Darragh, Teresa M.; Castle, Philip E.; Chelmow, David; Lawson, Herschel W.; Huh, Warner K.
Abstract : Objective: Vaginal cancer is an uncommon cancer of the lower genital tract, and standardized screening is not recommended. Risk factors for vaginal cancer include a history of other lower genital tract neoplasia or cancer, smoking, immunosuppression, and exposure to diethylstilbestrol in utero. Although cervical cancer screening after total hysterectomy for benign disease is not recommended, many women inappropriately undergo vaginal cytology and/or human papillomavirus (HPV) tests, and clinicians are faced with managing their abnormal results. Our objectives were to review the literature on vaginal cytology and high-risk HPV (hrHPV) testing and to develop guidance for the management of abnormal vaginal screening tests. Materials and Methods: An electronic search of the PubMed database through 2015 was performed. Articles describing vaginal cytology or vaginal hrHPV testing were reviewed, and diagnostic accuracy of these tests when available was noted. Results: The available literature was too limited to develop evidence-based recommendations for managing abnormal vaginal cytology and hrHPV screening tests. However, the data did show that (1) the risk of vaginal cancer in women after hysterectomy is extremely low, justifying the recommendation against routine screening, and (2) in women for whom surveillance is recommended, e.g., women posttreatment for cervical precancer or cancer, hrHPV testing may be useful in identification of vaginal cancer precursors. Conclusions: Vaginal cancer is rare, and asymptomatic low-risk women should not be screened. An algorithm based on expert opinion is proposed for managing women with abnormal vaginal test results. Abstract : After hysterectomy, HSIL and cancer of the vagina are rare; we propose a conservative approach to management of abnormal vaginal cytology and/or high-risk HPV tests. Supplemental digital content is available in the text.